Pelatihan Pemasaran Produk melalui Market Place dan Sosial Media di Sanggar Korangsang Manuwalu - Maria Helena Chandra; Leoni Octaviyona; Maria Angela Merici; Yohanes Frankoly; Friden Rizal (ABDISOSHUM: Jurnal Pengabdian Masyarakat Bidang Sosial dan Humaniora, 2026)
This Community Service (PKM) activity aims to improve digital literacy and online marketing skills of the Korangsang Manuwula Ikat Weaving Studio members in Poma Hamlet, Taka Plager Village, Nita District, Sikka Regency. The partners faced challenges in their limited understanding of social media and marketplaces as promotional tools, as well as the suboptimal utilization of the uniqueness of the traditional production process from cotton processing to natural dyeing in digital marketing strategies. The activity was conducted over five days in October 2025 using a participatory method that included field observations, socialization, training, mentoring, and documentation of the ikat weaving process. The results of the activity showed an increase in participants' ability to manage social media and marketplaces, create digital promotional accounts, and produce content based on local wisdom. Participants were able to showcase the cultural value of weaving through photos, product descriptions, and promotional materials on online platforms. The discussion revealed that the integration of digital marketing into local cultural products had a positive impact on market expansion, cultural identity strengthening, and the sustainability of the creative economy of the Sikka community. This activity demonstrated the effectiveness of collaboration between students and the community in strengthening digital capacity and preserving cultural heritage.